Sikap Kerjasama Mendekorasi Taplak Meja Dengan Kain Perca Kelas V SD Negeri 76 Kota Bengkulu - Salsabila, Mardenti; Anggraini, Dwi; Noperman, Feri (Universitas Bengkulu, 2025)
This study aims to describe the attitude of cooperation during the process of decorating tablecloths with patchwork in Grade V Fine Arts learning at SD Negeri 76 Bengkulu City. The research uses a qualitative descriptive method with Grade V students as the subjects. The main research instrument is the researcher, supported by observation guidelines for cooperative attitudes and work results, as well as interview guidelines. Data were collected through observation, interviews, and documentation, with data validity ensured through triangulation. The findings show that cooperative attitudes were assessed based on four indicators across three activity stages. In the stages of preparing tools and materials and creating patterns, Groups 1 and 3 did not demonstrate cooperative attitudes, particularly in respecting individual differences. These groups were not conducive to pattern making and showed a lack of listening to each other’s opinions. In contrast, Groups 2, 4, and 5 exhibited cooperative behavior by preparing thoroughly and following the teacher’s instructions, as well as listening to their group members’ ideas During the stages of designing, cutting, and sewing the patterns, most groups demonstrated improved cooperation. This was evident in the active participation of all members and in completing the tasks collaboratively.